Das Jahrhundert der Restaurationen: 1814 bis 1906 - Sellin, Volker (De Gruyter, 2014)
The year 2014 sees the 200th anniversary of Napoleon's downfall - and the restauration of the French monarchy under the house of Bourbon. With this as a starting point, Volker Sellin shows how the European monarchies restored and prolonged their reigns by giving their countries constitutions. This new angle results in an astonishing history of the 19th century in Europe from Spain to Russia